Continental Crossroads : Remapping U.S.-Mexico Borderlands History - Young, Elliott, 1967-; Truett, Samuel, 1966- (Book collections on Project MUSE., 2004)
Essays explore a transnational vision of the U.S./Mexico borderlands, and analyze this region's race, class, and gender inequalities in historical perspective.